1994
DOI: 10.1128/jvi.68.12.8209-8216.1994
|View full text |Cite
|
Sign up to set email alerts
|

Functional complementation of nuclear targeting-defective mutants of simian virus 40 structural proteins

Abstract: Structural proteins of simian virus 40 (SV40), Vp2 and Vp3 (Vp2/3) and Vpl, carry individual nuclear targeting signals, Vp3198_2o6 (Vp2316-324) and Vpll,, respectively, which are encoded in different reading frames of an overlapping region of the genome. How signals coordinate nuclear targeting during virion morphogenesis was examined by using SV40 variants in which there is only one structural gene for Vpl or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 31 publications
3
17
1
Order By: Relevance
“…We found that MPyV VP1 is efficiently transported into the cell nucleus when coexpressed with VP2 or VP3. The interchangeability of the NLS of polyomaviral structural proteins was described previously [31,32]; however, our results indicate that the NLS of the minor protein (VP2 or VP3) is absolutely indispensable for efficient VP1 nuclear localization. During infection, the complex of VP1 pentamer with one of the minor proteins is formed in the cytoplasm and then transported to the cell nucleus, where the virion assembly takes place.…”
Section: Discussionsupporting
confidence: 61%
“…We found that MPyV VP1 is efficiently transported into the cell nucleus when coexpressed with VP2 or VP3. The interchangeability of the NLS of polyomaviral structural proteins was described previously [31,32]; however, our results indicate that the NLS of the minor protein (VP2 or VP3) is absolutely indispensable for efficient VP1 nuclear localization. During infection, the complex of VP1 pentamer with one of the minor proteins is formed in the cytoplasm and then transported to the cell nucleus, where the virion assembly takes place.…”
Section: Discussionsupporting
confidence: 61%
“…pBS-SK(+), pEGFP-N3 (Clontech, Otsu, Japan), pFastBac1 (Invitrogen, Carlsbad, CA) and hSpt6WT/pFB (Endoh et al 2004) were used as 3000-, 4729-, 5000-and 10 000-bp circular DNAs, respectively. pSV40, containing the complete SV40 genome (Ishii et al 1994), and pLAPSN (Clontech) were also used in some experiments. These circular plasmid DNAs were linearized with appropriate restriction enzymes to obtain linear DNAs ranging in size from 2000 to 10 000 bp.…”
Section: Formation Of Various Atypical Structuresmentioning
confidence: 99%
“…The exposure of the R4 domain, which contains the nuclear localization signal of VP2/VP3 (5), is consistent with the ability of VP2 to aid in transporting a nuclear localization signal-defective VP1 to the nucleus (3). A similar observation has been made for the SV40 VP3 protein, in which the nuclear localization signal and VP1 interaction domain could be functionally separated (12,17). lon-exchange chromatography was used as an independent method to identify an interaction between VP1 and VP2/VP3, as well as to determine if biochemical properties of VP1 capsomeres changed with this interaction.…”
Section: Discussionmentioning
confidence: 70%
“…In vivo experiments with SV40 suggest that VP1, VP2, and VP3 interact prior to assembly to ensure the proper stoichiometry of capsid proteins within the nucleus (18,23,24). One hypothesis proposes that VP1 pentamers interact with VP2 and/or VP3 in the cytoplasm for cotransport into the nucleus (7,17). For example, temperature-sensitive tsB, tsC, or tsBC SV40 mutants, which have mutations in VP1, exhibit defects in both VP1 and VP2/VP3 subcellular localization at the nonpermissive temperature (18).…”
mentioning
confidence: 99%